Combined static-cyclic multi-axial crack propagation in cruciform specimens. (June 2019) - Giannella, Venanzio; Dhondt, Guido; Kontermann, Christian; Citarella, Roberto
Highlights: Crack growth in cruciform specimens depends on the static to cyclic loading ratio. Ratios belong 0.5 trigger crack growth orthogonal to the cyclic load. Ratios above 0.75 makes cracks grow orthogonal to the static load. Both FEM and DBEM predict crack growth well for both low and for high ratios. State-of-the-art approaches do not predict crack growth for ratios in-between well. Abstract: Two cracks, initiated from the opposite tips of a 45° inclined central notch, were considered in cruciform specimens made of Ti6246. A static load was applied along one arm of the specimen and a cyclic load (R = −1) was applied along the other arm. Crack propagation was carefully monitored by optical means for different ratios of static to cyclic load. The observed crack propagation was simulated using two numerical tools, involving two different mixed-mode crack propagation prediction methods. The experimental evidence shows that there is a switch in crack propagation direction from orthogonal to the cyclic load at low static load levels to orthogonal to the static load for high static load levels. Both numerical procedures were able to predict this switch, albeit at slightly different static to cyclic load ratios.